Intraoperative 3D imaging with cone-beam computed tomography leads to revision of pedicle screws in dorsal instrumentation: a retrospective analysis - Felix Zimmermann (BMC, 2021)
Abstract Background Correct positioning of pedicle screws can be challenging. Intraoperative imaging may be helpful. The purpose of this study was to evaluate the use of intraoperative 3D imaging with a cone-beam CT. The hypotheses were that intraoperative 3D imaging (1) will lead to an intraoperative revision of pedicle screws and (2) may diminish the rate of perforated screws on postoperative imaging. Methods Totally, 351 patients (age 60.9 ± 20.3 a (15–96); m/f 203/148) underwent dorsal instrumentation with intraoperative 3D imaging with 2215 pedicle screws at a trauma center level one. This study first evaluates intraoperative imaging. After this, 501 screws in 73 patients (age 62.5 ± 19.7 a; m/f 47/26) of this collective were included in the study group (SG) and their postoperative computed tomography was evaluated with regard to screw position. Then, 500 screws in 82 patients (age 64.8 ± 14.4 a; m/f 51/31) as control group (CG), who received the screws with conventional 2D fluoroscopy but without 3D imaging, were evaluated with regard to screw position. Results During the placement of the 2215 pedicle screws, 158 (7.0%) intraoperative revisions occurred as a result of 3D imaging. Postoperative computed tomography of the SG showed 445 (88.8%) screws without relevant perforation (type A + B), of which 410 (81.8%) could be classified as type A and 35 (7.0%) could be classified as type B. Fifty-six (11.2%) screws in SG showed relevant perforation (type C–E). In contrast, 384 (76.8%) screws in the CG were without relevant perforation (type A + B), of which 282 (56.4%) could be classified as type A and 102 (20.4%) as type B. One hundred and sixteen (23.2%) screws in the CG showed relevant perforation (type C–E). Conclusion This study shows that correct placement of pedicle screws in spine surgery with conventional 2D fluoroscopy is challenging. Misplacement of screws cannot always be prevented. Intraoperative 3D imaging with a CBCT can be helpful to detect and revise misplaced pedicle screws intraoperatively. The use of intraoperative 3D imaging will probably minimize the number of revision procedures due to perforating pedicle screws.